2008
DOI: 10.3171/jns/2008/108/4/0676
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of extratemporal epilepsy surgery among 154 adult patients

Abstract: Extratemporal epilepsy surgery is effective according to findings on long-term follow-up. The outcome at the first 2-year follow-up visit is a reliable predictor of long-term Engel Class I postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 72 publications
6
56
0
1
Order By: Relevance
“…One large study revealed that at 2 years follow-up, 50.3% were reported to have complete seizure freedom (or auras only) (Engel's Class I), 18.3% have Class II outcome, 17.7% have Class III outcome. This is greater than 50% reduction in seizures in 86% of the patients at 2 years follow-up [12]. Similar results were seen in patients who had MST as the primary procedure for extra-temporal onset seizures [1,[3][4][5][6].…”
Section: Discussionsupporting
confidence: 71%
“…One large study revealed that at 2 years follow-up, 50.3% were reported to have complete seizure freedom (or auras only) (Engel's Class I), 18.3% have Class II outcome, 17.7% have Class III outcome. This is greater than 50% reduction in seizures in 86% of the patients at 2 years follow-up [12]. Similar results were seen in patients who had MST as the primary procedure for extra-temporal onset seizures [1,[3][4][5][6].…”
Section: Discussionsupporting
confidence: 71%
“…1 Authors have suggested that the relative immaturity of the frontal cortex may render it more seizure prone and therefore promotes the development of multifocal seizures; this, in turn, may reduce the likelihood of achieving favorable surgical seizure outcome. 7 Additionally, the pathology that contributes to FLE is likely widespread in nature and is compounded by epileptic discharges spreading from other regions. Resection may therefore not be able to remove all possible causative foci.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological findings are typically reported in small-scale studies from individual centers, [13][14][15][16] or buried in larger series containing a full spectrum of patients among which only a small number was MRI-negative. 17,18 A few attempts at meta-analysis have been performed to better understand surgical outcome and factors such as pathology, surgery type, and seizure semiology in MRI-negative patients. Ansari et al 24 reported 95 pediatric extratemporal nonlesional epilepsy patients from 17 studies, and classified surgical pathology into three categories: cortical dysplasia, gliosis, and others (neuronal loss, encephalitis, polymicrogyria, ulegyria, chronic inflammation, and normal).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Studies specifically on the surgical pathology of MRI-negative patients, however, are limited to small-scale experiences of individual centers, [13][14][15][16] or cases buried in larger series containing both MRI-positive and -negative patients. 17,18 Moreover, with the advance in MRI technology over the last decade and the establishment of more uniform epilepsy MRI protocols, the definition of 'MRInegative' cases in recent studies may not be equivalent to earlier ones. The purpose of this study is to systematically review one institution's recent experience with the pathological substrates underlying strictly defined MRI-negative epilepsies.…”
mentioning
confidence: 99%